Influencing factors of consumer willingness to buy cattle meat: An analysis of survey data from three Brazilian cities (Acta Scientiarum. Animal Sciences, 2019)
Brazil is currently undergoing a process to establish new patterns of consumption habits and the implementation of a new concepts of meat quality. The process emphasizes the quality of information delivered to consumers, which is part of the new approach to meat quality and food safety. The objective of this article is to investigate the attributes considered important when buying beef, knowledge about the production process, labelling, cuts and characteristics of the animals. The study included 276 consumers in three Brazilian cities and their responses were examined in relation to the semi-structured form with fifteen spontaneous and stimulated questions. It was verified that the presentation of the product is regarded as the most important attribute at the time of purchase, they prefer to purchase meat in the butchers, and do not value the labelling of the product, which makes it difficult to identify and offer differentiated products or certificates. The frequency of consumption of beef increases with family income and the vast majority of consumers prefer low marbling meat regardless of the type of preparation. The consumer has little knowledge of more specialized cuts, since the product sold in the butchers has different cuts terminology.